TOWARDS A NEW NORMAL ERA: IMPLEMENTATION OF IMMIGRATION FUNCTION DURING THE COVID-19 PANDEMIC IN INDONESIA - Bima Yosua A Tarigan; Faridh Al Wajidi; K Karina (Journal of Law and Border Protection, 2021)
Immigration functions include immigration services, law enforcement, state security, and facilitating community welfare development. The implementation of these functions is carried out by the Directorate General of Immigration, which carries out the task of guarding the country's gates. However, during the Covid-19 pandemic, the Directorate General of Immigration is expected to be able to carry out the immigration function without neglecting the spread of the Covid-19 virus that is currently sweeping the world. Not to mention that there are problems that can threaten state security and national sovereignty as well as the decline in the country's economy during this pandemic. The formulation of the problem that will be examined in this paper is what forms of immigration function carried out by the Directorate General of Immigration and how the implementation of the implementation of the immigration function carried out during the Covid-19 pandemic. This writing uses a qualitative research method with a qualitative descriptive approach with combined data collection (inductive/qualitative). From the research results, it is known that the Covid-19 pandemic resulted in various policy changes that had an impact on the implementation of the immigration function. This issue must encounter by Directorate General of Immigration as an institution that is authorized to carry out the immigration function in Indonesia.